Potential correlation of oral flora with pemphigus vulgaris – A case control study - Bing-jie Li; Wen-xiu He; Hong Hua; Pan Wei (Journal of Dental Sciences, 2023)
Background/purpose: Oral flora is related to various immune-related diseases. Herein we explored the characteristics of oral flora in patients with pemphigus vulgaris (PV) and analyzed the correlation between oral flora and PV. Materials and methods: Twenty-two untreated patients with PV and 12 healthy controls (HC) were included in this case-control study. The characteristics of salivary microbiome were assessed by high-throughput sequencing using the 16S rRNA Illumina MiSeq approach, and differences between the PV and HC groups were determined. The Kyoto Encyclopedia of Genes and Genomes (KEGG) database was applied to screen key metabolic pathways and preliminarily explore potential mechanisms underlying PV occurrence and development. Results: The abundance of oral flora in the PV group was significantly lower than that in the HC group, and there were characteristic changes. The relative abundance of Prevotella and Agrobacterium in the PV group was significantly higher than that in the HC group (P < 0.05) and that of Neisseria, Lautropia, and Fusobacterium was significantly lower (P < 0.05). There was a linear correlation between Prevotella and serum Dsg3 level in PV. KEGG pathway analyses indicated significant differences in nine metabolic pathways between the PV and HC groups (P < 0.05), namely carbohydrate metabolism, digestive system, neurodegenerative disease, glycan biosynthesis and metabolism, drug resistance: antimicrobial, infectious disease: viral, circulatory system, excretory system, and nervous system. Conclusion: The oral flora of patients with PV presented characteristic changes, and several metabolic pathways were affected, including N-glycan biosynthesis and metabolism. Prevotella spp. appear to require the most attention in PV. We believe that oral flora dysbacteriosis contributes to PV occurrence and development.